The protein and energy intakes of thirty pre-school malnourished children with acute infections confined in the UP-PGH Medical Center Pediatric Ward. - Arenas, Amelia S.
A study was made on the actual protein and energy intakes of 30 pre-school age moderately and severely malnourished patients with acute infections confined in the pediatric ward of the UP-PGH Medical Center for a 6-month period. Each subject's dietary intake was determined after each meal every other day from the time of admission to about 2-4 weeks. The protein and energy intakes based on desirable and actual body weights were compared with the levels prescribed by physicians and those recommended by the Nutritionists-Dietitians Association of the Philippines (NDAP) for Malnourished children. The NDAP recommended intakes of protein and energy were 3.0 gm protein and 150 kcal per kg Desirable Body Weight (DBW) for the 1-3 year age group and 2.7 gm protein and 135 kcal per kg DBW for the 4-6 year age group. These levels are 50 more than the normal Recommended Dietary Allowances (RDA) for the respective age groups. It was noted that the physicians tended to prescribe the NDAP recommended levels of protein for the 1-3 year old children. However, their prescriptions for portein for the 4-6 year olds and for energy for both age groups tended to be lower than the NDAP recommended levels. The mean actual intakes of the 1-3 year old subjects were 50 kcal and 2.1 gm protein per kg DBW or 81 kcal and 3.4 gm protein per kg Actual Body Weight (ABW) per day. For the 4-6 year old subjects, the mean intakes were 50 kcal and 2.0 gm protein per kg DBW or 89 kcal and 3.5 gm protein per kg ABW per day. These intakes were significantly lower than the prescribed and recommended levels. The actual intake was 1/3 to 1/2 of the prescribed energy and 2/3 to 4/5 of the prescribed protein. The inadequacy of the actual intake was therefore more of energy than of protein. The mean protein energy of the prescribed diet was 11.8 whereas it was 16.2 for the actual intake. This more than satisfied the recommended 8 protein energy for children.
Thesis (Master of Science in Public Health, Nutrition)--Universit of the Philippines Manila.
Keywords: Diet therapy for children; Nutrition. -- Requirements; Enteral feeding of children